2007
DOI: 10.1677/joe-07-0010
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 3-regulated sarcoendoplasmic reticulum Ca2+-ATPase 2 expression by prolactin and glucocorticoids is involved in the adaptation of insulin secretory response during the peripartum period

Abstract: During pregnancy, the maternal endocrine pancreas undergoes, as a consequence of placental lactogens and prolactin (PRL) action, functional changes that are characterized by increased glucose-induced insulin secretion. After delivery, the maternal endocrine pancreas rapidly returns to nonpregnant state, which is mainly attributed to the increased serum levels of glucocorticoids (GCs). Although GCs are known to decrease insulin secretion and counteract PRL action, the mechanisms for these effects are poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
15
0
2
Order By: Relevance
“…We have found that phosphorylation of both STAT3 and AKT was activated by IL6, but only that of AKT was impaired by PA. In pancreatic b-cells, downregulation of STAT3 activity is mainly involved in the modulation of insulin secretion (Gorogawa et al 2004, Anhê et al 2007). On the other hand, it is well documented that the phosphatidylinositol 3-kinase (PI3K)/AKT signaling is a critical pathway regulating b-cell survival (Elghazi et al 2007), which is impaired by FFAs (Wrede et al 2002, Kharroubi et al 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that phosphorylation of both STAT3 and AKT was activated by IL6, but only that of AKT was impaired by PA. In pancreatic b-cells, downregulation of STAT3 activity is mainly involved in the modulation of insulin secretion (Gorogawa et al 2004, Anhê et al 2007). On the other hand, it is well documented that the phosphatidylinositol 3-kinase (PI3K)/AKT signaling is a critical pathway regulating b-cell survival (Elghazi et al 2007), which is impaired by FFAs (Wrede et al 2002, Kharroubi et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…1 mM glucose and 10% FBS) as described previously (Anhê et al 2007). For the time-course and doseresponse experiments, the cells were incubated for 30 min at 37 8C with Krebs-bicarbonate buffer (KBB) containing 0 .…”
Section: Rinm5f Cell Culture and Incubationmentioning
confidence: 99%
“…The contribution of gestational hormones on ␤-cell adaptation to pregnancy is highlighted by the demonstration that, even when the increased demand for insulin is compensated by exogenous insulin, changes in islet function characteristic of gestation still occur (36). However, the increases in both insulin secretion and ␤-cell proliferation are time-limited events that resume the nonpregnant features just after the delivery (5,38). It is likely that the reduction of intracellular calcium stores and SERCA2 expression in pancreatic islets mediate the decrease of maternal insulin secretion just after delivery (5,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the increases in both insulin secretion and ␤-cell proliferation are time-limited events that resume the nonpregnant features just after the delivery (5,38). It is likely that the reduction of intracellular calcium stores and SERCA2 expression in pancreatic islets mediate the decrease of maternal insulin secretion just after delivery (5,25). However, the precise mechanism by which the pancreatic ␤-cell switches from a high to a low proliferative status is much less comprehended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation